Rotoscoping - Bratt, Benjamin (Taylor and Francis, 2012)
Master what it takes to make your rotoscoping and digital painting blend seamlessly into each shot. Through illustrious four color presentation, the book features step-by-step instruction on the artistic techniques of rotoscoping and digital painting with lessons on: *Articulate mattes *Digital paint in moving footage *Motion tracking *Advanced rotoscoping and digital paint techniques, and much more It also features practical insight on the subject and industry, delving into: *The history and evolution of rotoscoping and the role of the rotoscoper *A typical day in the life of a rotoscoper *How to get a job as a rotoscoper Benjamin Bratt is a visual effects artist based out of Dallas, Texas who has worked as a digital artist on recent movies such as Underworld: Rise of the Lycans, Race to Witch Mountain, Obsessed, and The Proposal. He is currently the lead compositor at Radium/Reel FX in Dallas. Clients include the Dallas Cowboys, Coors, Ram Truck, and more. Benjamin has also taught Visual Effects and Rotoscoping classes at the Academy of Art.